State regulation of innovative activity in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
In this article the concept of an innovation, and also national innovative system of the Republic of Kazakhstan are considered. Definite purposes, the basic principles, the directions of the state support of innovative activity and the main operators of development of the sphere according to the legislation of the Republic of Kazakhstan. Stages of formation of national innovative system, some subjects of innovative activity and their feature, in particular science and technology parks and venture funds are studied. Following the results of the analysis of positive results of foreign countries in the field of innovations the big role of inclusion of higher educational institutions in process of creation of effective system of formation of innovations and their further functioning and development is noted. Within the state support of innovative activity it is important to give help at each stage of a design cycle in this connection, institutes of development carry out full financial, information and institutional support.
Keywords: innovations; state regulation; scientific potential; infrastructure; innovative project.